2016
DOI: 10.1021/acs.jpca.6b08438
|View full text |Cite
|
Sign up to set email alerts
|

Anion Binding of One-, Two-, and Three-Armed Thiourea Receptors Examined via Photoelectron Spectroscopy and Quantum Computations

Abstract: A benzene ring substituted with 1-3 thiourea containing arms (1-3) were examined by photoelectron spectroscopy and density functional theory computations. Their conjugate bases and chloride, acetate and dihydrogen phosphate anion clusters are reported. The resulting vertical and adiabatic detachment energies span from 3.93 - 5.82 eV (VDE) and 3.65 - 5.10 (ADE) for the deprotonated species and 4.88 - 5.97 eV (VDE) and 4.45 - 5.60 eV (ADE) for the anion complexes. These results reveal the stabilizing effects of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 35 publications
1
7
0
Order By: Relevance
“…Recently more examples have been reported, but this time affecting the anionic complexes. One of these cases involves thiourea/acetic acid complexes, which exhibit deprotonation of acetic acid despite the unfavorable differences in PA values. It was suggested that the resulting complex gains additional stability due to creation of additional intermolecular hydrogen bonds.…”
supporting
confidence: 70%
“…Recently more examples have been reported, but this time affecting the anionic complexes. One of these cases involves thiourea/acetic acid complexes, which exhibit deprotonation of acetic acid despite the unfavorable differences in PA values. It was suggested that the resulting complex gains additional stability due to creation of additional intermolecular hydrogen bonds.…”
supporting
confidence: 70%
“…Gas-phase proton affinity (PA), a thermodynamic quantity measuring the proton acceptance ability of an isolated base irrelevant to the surrounding environment, seems at first to provide a more appropriate criteria than acidity-basicity for predicting the preferential proton locations. , Indeed, considerable experimental evidence has been obtained in accordance with PA predictions. However, such an approach has been questioned in several studies of cationic systems, and recently also in anionic proton bound clusters. Those studies suggested that when the partner molecules are in close contact and experience strong mutual interactions, individual PA values will not convey a correct picture. We have recently shown that in an HSO 4 – ·H + ·HCOO – cluster, even the PA of HCOO – is about 36 kcal/mol larger than that of HSO 4 – , the cluster will still preferably adopt the form of H 2 SO 4 ·HCOO – , due to the resulting substantial electron delocalization and formation of two strong hydrogen bonds .…”
mentioning
confidence: 99%
“…Thiourea based tritopic assemblies have shown a lot of promise, for example, as an ionophores transferring ions and small molecules across hydrophobic membrane [1] . Incompletely N ‐substituted thiourea units offer interesting capabilities to these molecules acting as anion receptors due to their ability to form hydrogen bonds via NH‐groups [2–4] . Previous studies have shown that thiourea moieties are rather rigid and well suited to form halogen bonds, which offers possibilities to these molecules to form larger assemblies trough intermolecular weak interactions [5–7] .…”
Section: Introductionmentioning
confidence: 99%